Restorative Justice: An Alternative Approach to Addressing Domestic Violence in Indonesia - Suwito, Suwito; Mujito, Mujito; Darmawan, Didit; Inama, Inama; Saadi, Nailil Izzati (Innovative: Journal Of Social Science Research, 2025)
This study examines the effectiveness of domestic violence (DV) management in Indonesia, identifies barriers in the conventional legal system, and evaluates the potential for restorative justice. Through normative legal analysis, the study finds that shortcomings in legal implementation and erroneous social perceptions often hinder the justice process for victims. The findings suggest that restorative justice offers an alternative approach that is more humane and inclusive, potentially improving the DV management system. The study recommends significant legislative reform, increased capacity and sensitivity of law enforcement, and promotion of public education and awareness to effectively address DV.